Pengaruh Media Berbasis Video Interaktif Terhadap Pemahaman Siswa Pada Pembelajaran IPA Kelas V Sekolah Dasar - Fitria Fitria; Ratnawati Susanto (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
The problem that arises in learning process is that learners had not been able to comprehend learning directly taught by the teacher so that student learning outcomes do not meet the minimum completeness criteria. This study aim is to determine effects then results of using interactive video-based media on understanding sciences learning. The subjects of this study were 32 fifth grade students at SDN Duri Kepa 03. This research method was qualitative research such as questionnaire. Results of this study indicate that using interactive video-based media on students' understanding of science learning is very influential and student learning outcomes increase.